Physical and physiological quality of corn seeds (Research, Society and Development, 2020)
The aimed to evaluate the physical and physiological quality, as well the field initial performance of different maize seeds size, produced in two growing environments.  It were used seeds of the Amarelo maize (Zea mays L.) genotype, where it were produced in two growing environments at Rio Grande do Sul, in the crops season of 2016/2017. The environment that the seeds are produced and the seeds form affect the maize plants initial growth. Flat seeds are tend to have a better performance on field in relation to the initial growth. The seedlings originated from Entre Ijuís-RS present superiority to shoot length, stem diameter, roots dry matter and shoot dry matter, while Pelotas-RS determines the sieves yield. The round and small seeds present lower sieves yield, shoot length, root length and stem diameter of maize seedlings.